Tekoälyn käyttö pelinkehityksen tukena: kokemuksia pelialalta Suomessa - Krats, Mikael (2025)
Artificial intelligence has developed rapidly in recent years and has brought with it new ge- nerative tools that have the potential to revolutionize the application and gaming industry. This study examines what generative AI is and how it can be utilized in the gaming industry. At the same time, the use of artificial intelligence in the gaming industry is examined in practice by interviewing gaming industry professionals in Finland. Future of the gaming in- dustry with artificial intelligence and the challenges that artificial intelligence brings are also overviewed. The results of the study found that artificial intelligence can be utilized in idea creation, design, game content production, testing, analysis, learning and information searc- hing, among other things. The interviewees utilized artificial intelligence in programming and in game design but not in finished game assets. Artificial intelligence was also utilized in other tasks outside of game development, such as writing emails. Artificial intelligence can be assumed to play an increasingly larger role in the gaming industry in the future, bringing with it new threats and opportunities.